Estratégia de gerenciamento de microrrede trifásica com PV e bateria incluindo o corte de carga baseado na tensão do barramento CC - Soares, Luana Crispim Santiago (2022)
Microgrids based on photovoltaic generation do not have the capability to regulate voltage and frequency during islanded operation. In view of this, batteries are inserted to assist in the regulation of the microgrid as they present a quick and controllable response. The batteries can be connected individually or together with the photovoltaic generation, forming a hybrid unit, with the latter configuration having the advantage of being more cost-effective. They operate in a charge cycle when the PV generation is higher than the load and in a discharge cycle when the load is higher than the PV generation. However, this regulation capability is limited in charge limit, discharge limit, maximum SoC and minimum SoC situations. This gives rise to several operating states: 1. When the load demand of the microgrid is lower than the photovoltaic generation, the battery absorbs the excess power; or when the microgrid load demand is higher than the photovoltaic generation, the battery injects the deficit power; 2. When the load demand of the microgrid is lower than the photovoltaic generation and the battery is at the charge limit power, photovoltaic generation curtailment is performed; 3. When the load demand of the microgrid is lower than the photovoltaic generation and the battery is at maximum SoC, photovoltaic generation curtailment is performed; 4. When the load demand of the microgrid is higher than the photovoltaic generation and the battery is at the discharge limit power, load shedding is performed; 5. When the load demand of the microgrid is higher than the photovoltaic generation and the battery is at minimum SoC, load shedding is performed. In state 1, the battery is responsible for regulating the DC-bus voltage by injecting or absorbing power, while the photovoltaic works in MPPT. In states 2 and 3, the battery becomes unable to regulate the DC-bus voltage, thus, the photovoltaic leaves the MPPT and becomes responsible for regulating this voltage. In states 4 and 5, the battery becomes unable to regulate DC-bus voltage and the photovoltaic generation must remain in MPPT, therefore, to control the DC-bus and maintain the balance of the microgrid, load shedding must be performed. In contrast to the existing methods in the literature, this work proposes a method for load shedding based on the DC-bus voltage, allowing the control not to depend on the frequency estimation based on PLL, which has disadvantages in systems where high performance and high reliability are needed. Therefore, the proposed method has the advantage of relying only on local voltage measurement. To implement and test the proposed load shedding strategy, it was necessary to develop the modeling of the photovoltaic generation source and the battery, as well as its boost and bidirectional buck-boost converters. In the same way, the grid filter and the VSI were modeled, in addition to the loads, based on the constant impedance model. Finally, the control strategy was implemented to meet the different operating states of the microgrid. The effectiveness of the proposed method is validated under different conditions through simulations in MATLAB/Simulink software.